Liberalism, Liberalization and Their Impacts of Muslim Education (Special Case of Indonesian Intellectuals) - Hamid Fahmy Zarkasyi (Universitas Darussalam Gontor, 2012)
This paper is aimed at elucidating the liberalization of Muslim world and its impact on education. For that purpose the author traces at the outset the origin and the basic concept of liberalism, which is of postmodern Western worldview, including the concept of religious liberalism. The impact of liberalism in general is as wider as the meaning of liberalism in Western sense of the words. However, this paper confines only on the study of their impact on Muslim education with special emphasis on national education policy and on religious thought which in turn would affect curriculum development. Liberalization of religious thought appears, inter alia, through the introduction of the doctrine of relativity of truth, religious pluralism, gender equality and deconstruction of shari’ah and the likes. All those religious discourse conceptually hinder the development of curriculum and the teaching strategy of moral inculcation to the students.